2017
DOI: 10.5152/tud.2017.34793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic efficacy of strain elastography in infertile population with normal and abnormal semen parameters

Abstract: Objective: The aim of the present study was to investigate the diagnostic value of strain elastography (SE) of testicular tissues in infertile population. We also evaluated the correlation between SE results with semen parameters and hormone profiles of the patients. Material and methods:A total of 61 patients and 122 testes were evaluated. Patients who were evaluated in an andrology outpatient clinic with the diagnosis of infertility and referred to radiology department for investigation of reproductive organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…All grayscale and SWE examinations were performed using an Aplio 500 Platinum (Canon, Tokyo, Japan) US unit. The measurements were conducted using a linear array high-frequency transducer (11)(12)(13)(14). The testicular volumes were calculated from 2-dimensional images using the prolate ellipsoid method based on the formula: volume=length×width× height×0.523.…”
Section: Methodsmentioning
confidence: 99%
“…All grayscale and SWE examinations were performed using an Aplio 500 Platinum (Canon, Tokyo, Japan) US unit. The measurements were conducted using a linear array high-frequency transducer (11)(12)(13)(14). The testicular volumes were calculated from 2-dimensional images using the prolate ellipsoid method based on the formula: volume=length×width× height×0.523.…”
Section: Methodsmentioning
confidence: 99%
“…Pinggera et al found that the RI measurement of the intratesticular arteries showed an increased testicular vascular resistance in patients with pathological sperm characteristics in comparison to the control group (Pinggera et al, ). However, in a different study, no difference was observed (Kucukdurmaz et al, ). In our study, the median RI value was found to be higher in the patients with varicocele and bad seminal parameters than in the patients in the control group.…”
Section: Discussionmentioning
confidence: 89%
“…Kucukdurmaz et al compared two groups with normal and abnormal sperm parameters using elastography; they found that the SR ratio was significantly lower in the group with abnormal seminal parameters. They also found that the average testicular volume was lower in the group with abnormal seminal parameters (Kucukdurmaz et al, ). In a study in which (Dede et al ( compared the elastography images of patients with varicocele and without varicocele, the SR value of the varicocele group was lower.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations